Climatic control of radial growth of Cedrela montana in a humid mountain rainforest in southern Ecuador - Bräuning, Achim; Volland-Voigt, Franziska; Burchardt, Iris; Ganzhi, Oswaldo; Nauß, Thomas; Peters, Thorsten (ERDKUNDE, 2009)
Cedrela montana is a deciduous broad-leaved tree species growing in the humid mountain rainforests of southern Ecuador. High-resolution dendrometer data indicate a regular seasonal growth rhythm with cambial activity during January to April. Amplitudes of daily radial stem diameter variations are correlated with the amount of the maximum daily vapour pressure deficit. During humid periods, daily stem diameter variations are considerably smaller than during drier periods. This indicates that cambial activity is limited by available moisture even in such a very humid mountain climate. Wood anatomical studies on microcores show the formation of a marginal parenchyma band at the beginning of the growth period. This parenchyma band can be used to delineate annual growth rings. We were able to establish the first ring-width chronology from Cedrela montana which covers the time until 1840. However, the chronology is presently statistically robust back to 1910 only. Correlation functions calculated with NCEP/NCAR data indicate a significantly positive relationship of tree growth with temperatures during the growth period during January to April. However, only 8% of the growth variance is explained by this climatic factor. In the future, this relationship may be useful to reconstruct past temperature conditions of the study area.